Caso estomatológico - Amorim,José M. S. (2011)
A 17 year-old-girl was referred to our department because of facial swelling, trismus and pain. She had had previous drainage of the swelling and was on antibioticotherapy. Ludwigs angina was diagnosed; the orthopanthomagraphy showed dental abscess and caries. She had intravenous antibiotherapy and dental extraction with resolution of the condition.